Transcultural Communication Strategies in Nursing with Multicultural Clients in Hospital Settings: A Systematic Literature Review - Reiza Agustina Wulandari; Nurfika Asmaningrum; Anisah Ardiana (Universitas Pendidikan Indonesia, 2022)
ABSTRACTIntroduction: A lack of nurse understanding of cultural diversity during nurse-patient communication may cause conflicts and misunderstandings. Objectives: To analyze nurse transcultural communication strategies with multicultural clients in hospitals. Methods: Systematic literature review incorporating four databases, including PubMed, Science Direct, Google Scholar, and ProQuest. Assessed Article quality based on JBI and MMAT. Results: A total of 47.848 articles were identified, and twelve articles analyzed highlight ten transcultural communication strategies, including the usage of language translators and interpreters, communication skills training, cultural competency training, initiative to learn a new culture, clarity of communication, doing self-reflection, familiarizing to the patient, developing confidence, spending more time to consult, respecting and appreciating patient. Discussion: implementing transcultural communication strategies during nurse-patient interactions is important to achieve therapeutic communication goals. Conclusion: Transcultural communication enables nurses to understand and respond to patient needs effectively. The study suggests that nurses develop transcultural communication skills and competencies to practice intercultural communication during clinical care.ABSTRAKPendahuluan: Kurangnya pemahaman perawat atas keragaman budaya pasien selama komunikasi antar perawat-pasien dapat menyebabkan konflik dan kesalahpahaman, sehingga dibutuhkan strategi dalam komunikasi transkultural. Tujuan: Menganalisis strategi komunikasi lintas budaya perawat dengan klien multikultural di rumah sakit. Metode: Tinjauan literatur sistematis yang menggabungkan empat database termasuk PubMed, Science Direct, Google Scholar, dan ProQuest. Kualitas artikel dinilai berdasarkan JBI dan MMAT. Hasil: Sebanyak 47.848 artikel berhasil diidentifikasi. Dua belas artikel yang dianalisis ditemukan sepuluh strategi komunikasi lintas budaya meliputi: penggunaan penerjemah dan juru bahasa, pelatihan keterampilan komunikasi, pelatihan kompetensi budaya, memperjelas penekanan komunikasi, inisiatif untuk mempelajari budaya baru, mampu merefleksikan diri, mampu mengakrabkan diri, mengembangkan kepercayaan diri, meluangkan lebih banyak waktu untuk konsultasi, menghormati dan menghargai klien. Diskusi: Penerapan strategi komunikasi lintas budaya selama interaksi perawat-pasien penting untuk mencapai tujuan komunikasi terapeutik. Simpulan: Komunikasi lintas budaya memungkinkan perawat untuk secara efektif memahami dan menanggapi kebutuhan pasien. Studi ini menyarankan perawat harus mengembangkan kompetensi keterampilam komunikasi lintas budaya untuk mempraktikan komunikasi antar budaya selama perawatan klinis.